Association of donor hepatitis C virus infection status and risk of BK polyomavirus viremia after kidney transplantation. Issue 2 (6th October 2021) - Molnar, Miklos Z.; Potluri, Vishnu S.; Schaubel, Douglas E.; Sise, Meghan E.; Concepcion, Beatrice P.; Forbes, Rachel C.; Blumberg, Emily; Bloom, Roy D.; Shaffer, David; Chung, Raymond T.; Strohbehn, Ian A.; Elias, Nahel; et al.
Abstract : Kidney transplantation (KT) from deceased donors with hepatitis C virus (HCV) into HCV‐negative recipients has become more common. However, the risk of complications such as BK polyomavirus (BKPyV) remains unknown. We assembled a retrospective cohort at four centers. We matched recipients of HCV‐viremic kidneys to highly similar recipients of HCV‐aviremic kidneys on established risk factors for BKPyV. To limit bias, matches were within the same center. The primary outcome was BKPyV viremia ≥1000 copies/ml or biopsy‐proven BKPyV nephropathy; a secondary outcome was BKPyV viremia ≥10 000 copies/ml or nephropathy. Outcomes were analyzed using weighted and stratified Cox regression. The median days to peak BKPyV viremia level was 119 (IQR 87–182). HCV‐viremic KT was not associated with increased risk of the primary BKPyV outcome (HR 1.26, p = .22), but was significantly associated with the secondary outcome of BKPyV ≥10 000 copies/ml (HR 1.69, p = .03). One‐year eGFR was similar between the matched groups. Only one HCV‐viremic kidney recipient had primary graft loss. In summary, HCV‐viremic KT was not significantly associated with the primary outcome of BKPyV viremia, but the data suggested that donor HCV might elevate the risk of more severe BKPyV viremia ≥10 000 copies/ml. Nonetheless, one‐year graft function for HCV‐viremic recipients was reassuring. Abstract : Retrospective analysis of a multi‐center deceased donor kidney transplant cohort shows that recipients of hepatitis C‐viremic kidneys versus recipients of hepatitis C non‐viremic kidneys have comparable rates of BK virus infection but increased rates of high level BK viremia, suggesting that donor‐derived hepatitis C infection may promote susceptibility to other viral infections.